A Big Thank You to our Reviewers in the Past Year! (Hormone and Metabolic Research, 2018)
Good reviewers are essential to the success of any journal and peer review is a major pillar of science. We are grateful to those mentioned below to have dedicated their time and expertise to help our authors improve and refine their manuscripts and support the Editors in the decision making process in the past year.The following received out Top Reviewer of the Year award:We wish all our readers, reviewers, authors and friends a happy and prosperous 2018!Matthias Schott, MD, PhD Stefan R. Bornstein, MD, PhD Constantine A. Stratakis, MD, D(med)Sci Editors-in-Chief